Radiation hard 3D silicon pixel sensors for use in the ATLAS detector at the HL-LHC. (1st August 2022) - Heggelund, A.L.; Huiberts, S.; Dorholt, O.; Read, A.L.; Rohne, O.; Sandaker, H.; Lauritzen, M.; Stugu, B.; Kok, A.; Koybasi, O.; Povoli, M.; Bomben, M.; et al.
Abstract: The High Luminosity LHC (HL-LHC) upgrade requires the planned Inner Tracker (ITk) of the ATLAS detector to tolerate extremely high radiation doses. Specifically, the innermost parts of the pixel system will have to withstand radiation fluences above 1 × 10 16 neq cm -2 . Novel 3D silicon pixel sensors offer a superior radiation tolerance compared to conventional planar pixel sensors, and are thus excellent candidates for the innermost parts of the ITk. This paper presents studies of 3D pixel sensors with pixel size 50 × 50 μm 2 mounted on the RD53A prototype readout chip. Following a description of the design and fabrication steps, Test Beam results are presented for unirradiated as well as heavily irradiated sensors. For particles passing at perpendicular incidence, it is shown that average efficiencies above 96% are reached for sensors exposed to fluences of 1 × 10 16 neq cm -2 when biased to 80 V.